PENILAIAN SIMILAR DAN TIDAK SIMILAR PADA DESAIN PRODUK BERDASARKAN SKEMA KONSEPTUAL TERBANGUNNYA FORM DARI SUATU OBJEK: SIMILAR AND UNSIMILAR ASSESSMENTS IN PRODUCT DESIGN BASED ON THE SCHEMA OF THE FORM OF AN OBJECT - Sapta Rika Suprihatin; Drajatno Widi Utomo; Ahadiat Joedawinata (Universitas Trisakti, 2024)
Similar and Unsimilar Assessments in Product Design Based on the Schema of the Form of an Object. In the process of checking novelty at the Directorate General of Intellectual Property (DGIP), a similar and not similar assessment is carried out on a product with a pre-existing product. However, there are often discrepancies in assessments between officers. So that the conceptual scheme for building the form of an object is used in this study. Based on this concept, aspects of efforts to achieve efficiency and physical performance, aspects of efforts to achieve system control, tempo, production costs and production capacity and aspects of efforts to achieve representation of aesthetic and symbolic content can be a differentiator between one product and another. Using a descriptive qualitative method approach, two potted plants which were the subject of debate in the assessment of similar and not similar by the officers were appointed as objects of research. The results of the research are recommendations for evaluating similar and not similar which can be used as a basis for assessing design novelty at DGIP.